Respuesta :

Answer:

x= 2/3-y/z

Step-by-step explanation:

step1: 3x+y/z=2

step2: 3x= 2-y/z

step3: 3x/3 = (2-y/z)/3

step 4: x= 2/3- y/z

Answer:

[tex]x=\frac{2z-y}{3z}[/tex]

Step-by-step explanation:

Given:

[tex]3x+\frac{y}{z} =2[/tex]

Solution:

[tex]3x+\frac{y}{z} =2[/tex]

Multiply both sides by [tex]z[/tex]:

[tex]3xz+y=2z[/tex]

Take [tex]+y[/tex] to the other side:

[tex]3xz=2z-y[/tex]

Divide [tex]3z[/tex] by both sides:

[tex]\frac{3xz}{3z} =\frac{2z-y}{3z}[/tex]

[tex]x=\frac{2z-y}{3z}[/tex]